PENGARUH BIAYA AGENSI, KEBIJAKAN HUTANG DAN TAHAP DAUR HIDUP PERUSAHAAN TERHADAP KEBIJAKAN DEVIDEN - Jayanti, Esih (JURNAL EKONOMI, 2016)
The objective of this research is to explores the dividend policy of the listed firms in the Indonesian Stock Exchange of 2011-2015 period. The Agency theory argues that the dividend policy will reduce the agency cost and problems. The percentage of institutional ownership of a common stock firm is used as a proxy for agency cost and it can be used as a mechanism to reduce agency problems. The research is, also, to examine the effect of debt policy towards dividend policy on a firm life cycle that is growth and mature as Agency theory does. The totally of sample are 44 of listed firm in Indonesia Stock Exchange. Group of growth firm are 8 and group of mature firm are 34. Classifying of firm become growth and mature firms group used sales growth for five years. The result of this research indicates that there is a support on agency theory. Agency cost is found the negative and significant effect toward dividend policy. Moreover, in the debt policy has the positive and significant effect toward dividend policy in mature phase and has a negative effect when is on growth phase.Key Words: Agency Cost, Institutional Ownership, Dividend Policy, Debt Policy Firm Life cycle.